Intensive Intraocular Pressure-Lowering Treatment in Open-Angle Glaucoma Patients: Critical Review - Mega Ayu Naily Rahmatika; Hilmy Fawwas Al Hakim (PT. Anagata Sembagi Education, 2026)
Glaucoma is a progressive optic neuropathy and one of the leading causes of irreversible visual field loss and blindness worldwide, with intraocular pressure (IOP) representing the most important modifiable risk factor. The Glaucoma Intensive Treatment Study (GITS) evaluated the effectiveness of intensive IOP-lowering therapy compared with standard treatment in patients with newly diagnosed open-angle glaucoma. This critical review aimed to evaluate the study’s methodology, findings, validity, strengths, limitations, and clinical implications for determining initial therapeutic strategies in open-angle glaucoma. A critical appraisal was conducted of the randomized controlled trial by Bengtsson et al. (2024), published in the American Journal of Ophthalmology, involving 242 treatment-naïve patients. Participants in the intensive treatment group received a combination of IOP-lowering medications and laser trabeculoplasty, whereas the standard treatment group received monotherapy. Intensive therapy achieved a significantly lower median IOP (14 mmHg vs. 17 mmHg) and reduced glaucoma progression (11% vs. 21%; p = 0.03). However, the primary endpoint, predicted lifetime Visual Field Index (VFI), showed no statistically significant difference (87.1% vs. 79.3%; p = 0.15), and the reduction in visual field deterioration was also not significant (p = 0.09). Moreover, adverse events occurred more frequently in the intensive treatment group (36% vs. 25%). Overall, GITS demonstrates that intensive IOP-lowering therapy improves IOP control and reduces glaucoma progression; however, its routine implementation cannot yet be universally recommended because of the absence of significant benefit in the primary outcome and the higher incidence of treatment-related adverse effects. Therapeutic decisions should therefore be individualized according to baseline IOP, disease severity, risk of progression, patient age, and the balance between potential benefits and harms.